Self-Efficacy On The Learning Independence Of Class Xii Students Of Culinary Smk Negeri 9 Padang - Andriyani, Monica; Gusnita, Wiwik; Kasmita, Kasmita; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This research is based on the low learning independence of students as seen from learning initiatives and responsibilities and students do not have self-efficacy as seen from self-confidence, attitude and persistence in completing tasks. This study aims to describe students' self-efficacy, describe learning independence, and analyze the influence of self-efficacy on the learning independence of grade XII students of Culinary SMK Negeri 9 Padang.  This type of research is quantitative with a regression approach, The population in this study is grade XII students majoring in Culinary at SMK Negeri 9 Padang as many as 224 students. The research sample was 144 students with random sampling technique. Data collection was carried out by distributing questionnaires directly using a likert scale that has been tested for validity and reliability. The data were analyzed using descriptive analysis. The results of the study showed that the self-efficacy of students in grade XII Culinary as a whole was in the medium category with a percentage of 40%, and the learning independence of students was in the medium category with a percentage of 35%. The results of the hypothesis test can be concluded that there is a positive and significant relationship between self-efficacy and learning independence of grade XII Culinary students at SMK Negeri 9 Padang.